Prioritizing geriatrics in medical education improves care for all. Issue 1 (31st December 2022) - Rentsch, Samuel; Vitale, Caroline A.; Zietlow, Kahli
ABSTRACT: Within the United States, there is a deficit of Geriatricians providing care for older adults, and this deficit will only grow as the population continues to age, meaning all clinicians, particularly Internal Medicine (IM) and Family Medicine (FM) trained physicians, will provide the bulk of primary care for older adults. However, geriatric training requirements for clinicians fall short, and in the case of IM were reduced as of 2022. Serving as a call to action, this article provides insight on ways to enhance geriatric education for all graduate medical trainees, utilizing both conventional teaching and newer, non-traditional media, such as national online journal clubs, podcasts, and online teaching curricula, as well as expanding sites of training to include evidence-based models of care, such as the Program of All-Inclusive Care for the Elderly (PACE). Providing geriatric education improves care for older adults and our future selves, ensuring trainees are prepared to care and advocate for this diverse and often vulnerable population.